Los métodos utilizados por los docentes y el desarrollo de destrezas con criterio de desempeño del bloque curricular de números y funciones, en los estudiantes del primer año de bachillerato general unificado del colegio de bachillerato Paltas, cantón Paltas, provincia de Loja, período 2013-2014. Lineamientos alternativos - Vire Gonzalez, Fausto Enrique (2015)
The present research on the methods used by teachers and skills development with performance criteria Curricular Block Numbers and Functions, in freshmen Unified High School General High School College Paltas, Paltas Canton, and Province of Loja, 2013-2014 Period. Alternative Guidelines, had as a general objective and three specific objectives: the general, contribute to the teaching-learning curriculum block of numbers and functions, through the analysis of the methods used by teachers and their impact on achieving skills with performance criteria in freshmen General Unified Baccalaureate College High School Paltas, 2013-2014. And determine the specific methods used by teachers to achieve skills with performance criteria curricular Numbers and Functions Freshmen High School General High School Unified School Paltas, identify the skills developed with performance criteria Number of curricular and Functions for freshmen Unified High School General High School College Paltas and propose alternative guidelines to improve the use of methods for achieving skills with performance criteria curricular Numbers and Functions for freshmen Unified High School General High School College Paltas. By applying a survey and analysis and interpretation of results the following are highlighted: Majority of teachers of Mathematics of the first year of General Unified School used the deductive method, logical method and the comparative analog method while partly works with the inductive method. The Mayor of the teachers do not use the heuristic method thus imposing the student to observe without question what he teaches, on the assumption that this is the truth and only fit absorb Most students of the First Year General Unified School are limited to making and answering questions, the seats are kept in columns and rows. Most students of the First Year General Unified School have failed to develop the skill with performance criteria to solve a system of two equations in two variables graphically and analytically. Results with which one could deduce that the methods used by teachers in the teaching-learning process in the block of numbers and functions poorly affect the development of skills with performance criteria in the curricular Numbers and Functions students first year of General Unified School High School College Paltas.